Assessing good governance practices and development nexus: an application of structural invariance analysis / Ibrahim Abiodun Oladapo ... [et al.] - Oladapo, Ibrahim Abiodun; Omar, Normah; Ab Rahman, Asmak; Arshad, Roshayani; Mohammed Hamoudah, Manal; Abdurraheem, Abdulazeez Adewuyi (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2019)
This paper aims to assess good governance and development nexus based on the Theory of Maqāsid al Sharī'ah (TMS). The central hypothesis of the paper is that good governance; with a specific focus on human rights and social justice has a significant relationship with human development including factors like education, health, and income all emerging from of the essentials of Sharī'ah. The paper employed survey questionnaire to collect data from 384 respondents comprising Muslims in South-western Nigeria. A stratified random sampling technique was used. The findings show that TMS is effective in predicting the direction of relationship between good governance and human development. The findings further show that the model is invariant across gender groups. This paper highlights the applicability of the constructs of TMS model into human development research. It also recommends strategic policy direction for the policymakers.